2011
DOI: 10.1097/mjt.0b013e3181b7b8c0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for the Treatment of Primary Sclerosing Cholangitis

Abstract: Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease that is associated with considerable morbidity and mortality. The disease etiopathogenesis has not been well defined. Several observations suggest that portal bacteremia or chronic bile duct infection may be factors that could play a role in the pathogenesis of the disease. Clinical trials have tested different treatments for PSC but without convincing evidence of benefit. Liver transplantation is the only available therapeutic option … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…However, these agents may not control the disease in the long term, and chronic cholestasis may progress. Antibiotics, such as azithromycin and metronidazole, have been shown to improve liver enzymes in adults with PSC [24]. Oral vancomycin has also been shown to improve liver enzymes, erythrocyte sedimentation rate, and clinical symptoms in 14 children, especially in those without cirrhosis [25].…”
Section: Medical Therapymentioning
confidence: 98%
“…However, these agents may not control the disease in the long term, and chronic cholestasis may progress. Antibiotics, such as azithromycin and metronidazole, have been shown to improve liver enzymes in adults with PSC [24]. Oral vancomycin has also been shown to improve liver enzymes, erythrocyte sedimentation rate, and clinical symptoms in 14 children, especially in those without cirrhosis [25].…”
Section: Medical Therapymentioning
confidence: 98%
“…Since the initial case series of antibiotics in PSC [56], several small studies have been published, the majority within the past 10 years [1,57]. Three of these were prospective clinical trials (Table I), all three of which showed reduction in the biomarker serum alkaline phosphatase (ALK) with antibiotic treatment (weighted average reduction of 41%) [19,58,59].…”
Section: Clinical Experience With Oral Antibiotics In Pscmentioning
confidence: 99%
“…Chronic fatigue, jaundice, itching, malabsorption, cirrhosis, enlarged liver, enlarged spleen, weight and appetite loss, and infection of the bile duct are the most common symptoms of primary sclerosing cholangitis (Miura and Miyachi 2009;Bowlus 2011;Elfaki and Lindor 2011;Ibrahim and Lindor 2011;Singal and others 2011;Azizi and others 2012). There are different medications for the treatment of primary sclerosing cholangitis such as cholestyramine (Mendes and Lindor 2010), ursodeoxycholic acid (Lindor and others 2009), antibiotics (Elfaki and Lindor 2011) (for treatment of bile duct infections), and some immunosuppressive drugs such as prednisone, azathioprine, cyclosporine, and methotrexate (Tabibian and Lindor 2013). Treatments with some vitamins such as vitamin D, vitamin E, vitamin A, and vitamin K have also shown to have some beneficial effects (Ibrahim and Lindor 2011).…”
Section: Primary Sclerosing Cholangitismentioning
confidence: 99%